HUBUNGAN PELAKSANAAN SENAM HAMIL PADA IBU HAMIL 36 MINGGU DENGAN LAMA PROSES PERSALINAN KALA I DAN KALA II DI BPS â€œBâ€ BUKITTINGGI TAHUN 2014 - Syelvi, Syelvi; Mutia Felina, Mutia Felina (LPPM Universitas Prima Nusantara Bukittinggi, 2015)
Maternal Mortality occurred due to complications of pregnancy and childbirth, caused by prolonged labor. Efforts to reduce the incidence of prolonged labor, namely the implementation of pregnancy exercise in pregnancy may help reduce the incidence of length delivery, lowering maternal anxiety in the face of strengthening the role of labor contractions, maintain flexibility of the muscles of the abdominal wall, the pelvic floor muscles and hold additional pressure related with childbirth.The arms of this study is to determine the